Evaluating the Differences Between Fluorescein Tear Break-up Time and Noninvasive Measurement Techniques - Itokawa, Takashi; Suzuki, Takashi; Koh, Shizuka; Hori, Yuichi (Eye & contact lens, 2023)
To compare fluorescein tear break-up time (BUT) and noninvasive BUT measured using interferometry and corneal topography. We investigated 34 eyes of 34 patients with dry eye (mean age 39.2±8.3 years) and 16 eyes of 16 non-dry eye subjects (33.5±6.5 years). Tear film stability was measured using fluorescein BUT, noninvasive BUT (NIBUT)-DR1 with an interferometer, and noninvasive keratographic BUT (NIKBUT)-first and average using corneal topography. Correlations between fluorescein BUT and noninvasive BUT parameters were determined statistically. The noninvasive BUTs were compared between the dry eye and non-dry eye groups. The agreement between fluorescein and noninvasive BUTs was described using Bland-Altman analysis. Fluorescein BUT was significantly correlated with NIBUT-DR1, NIKBUT-first, and NIKBUT-average. The Bland-Altman analysis revealed bias and 95% limits of agreement between fluorescein BUT and noninvasive BUTs as follows: NIBUT-DR1: 2.07 s, -5.33 to 9.46 s; NIKBUT-first: 3.39 s, -5.46 to 12.24 s; NIKBUT-average: 6.61 s, -1.58 to 14.79 s. The noninvasive BUTs were significantly different between the two groups. When NIBUT-DR1, NIKBUT-first, and NIKBUT-average with Bland-Altman correction were used as an index for dry eye, the cut-off values were 7.1, 8.4, and 11.6 s, respectively. The sensitivities were 0.735, 0.818, and 0.727 and specificities were 0.500, 0.437, and 0.562, respectively. Fluorescein BUT and noninvasive BUTs were significantly correlated, and noninvasive BUTs had higher values than fluorescein BUT. Considering the differences between fluorescein BUT and noninvasive BUTs, noninvasive methods can be used as effective tool for diagnosing dry eye.